Research on Effective Approaches to Precise Ideological and Political Education Work for College Counselors in the New Era - Li, Yang (Education Insights, 2026)
Ideological and political education in universities during the new era faces evolving developmental contexts and heightened educational demands. With rapid advancements in information technology, increasing diversity of student perspectives, and ongoing digital transformation in higher education, traditional approaches to ideological education have become inadequate for meeting the personalized growth needs of contemporary students. Precision-oriented ideological education, emerging as a key innovation direction for university political work, emphasizes student-centered strategies through precise identification, targeted delivery, effective implementation, and accurate evaluation to significantly enhance educational quality and efficiency. University counselors, serving as the primary organizers and implementers of ideological education as well as daily student management, play pivotal roles in advancing this modern approach. Based on contemporary requirements for ideological education development, this comprehensive study analyzes the core essence and intrinsic value of precision-oriented education. Furthermore, it identifies the practical challenges currently faced by counselors, such as resource allocation and technological adaptation. To address these issues, the research establishes a systematic framework comprising 'precise identification, targeted delivery, effective implementation, and accurate evaluation,' and proposes actionable optimization pathways. The research concludes that university counselors should fully leverage their critical functions in ideological guidance, value cultivation, and personal development support. By doing so, they can elevate the overall quality of precision-oriented education, promote holistic student growth, and provide robust support for fulfilling the fundamental academic mission of fostering virtue through education.